FAO-GLF Digital Forum: The beneficial role of extensive grazing for the restoration of dryland ecosystems - Louhaichi, Mounir (Food and Agriculture Organization of the United Nations, 2023)
The digital forum is hosted jointly by the Global Landscapes Forum and the Food and Agriculture Organization of the United Nations (FAO). Dr. Mounir Louhaichi was invited to contribute to the FAO-GLF Digital Forum. He provided a live professional presentation on the beneficial role of extensive grazing for the restoration of dryland ecosystems where he presented a case study from Tunisia.